Skal idrætten fortsat have sit eget retssystem? En analyse af det idrætsretlige system set i lyset af Anja Andersen-sagen - Rasmussen, Jens Bertel (Forum for Idræt, 2007)
Artiklen handler om, i hvilket omfang idrætten kan betragtes som et isoleret område med eget retssystem, eller hvorvidt de civile domstoles behandling skal findes anvendelse for sportsudøvere, ledere og trænere i de sager, der kan opstå i forbindelse med idrætsudøvelse. Artiklen gennemgår behandlingen af den såkaldte Anja Andersen sag. Jens Bertel Rasmussen: Should athletic associations continue to have their own system of justice? An analysis of the system of justice within sports associations focusing on the Anja Andersen-case Sports associations have their own system of justice, containing rules and laws on punishment and bans. This article focuses on the issue of whether sports associations can be looked upon as being an isolated area, containing values and standards of its own or if the laws and values of society apply to athletes, leaders and coaches as well. Are certain fundamental legal rights being violated, when sports associations sentence either individuals, teams or associations to fines or bans? Through an analysis of the system of justice in the sports associations and an analysis of the legal rights and rules in question, the article concludes that rules and laws should apply to the sports associations in the same degree as they apply in society in general. Having said that, there are certain matters surrounding sports associations that entail different rules and systems to apply. The author of the article therefore concludes, that a separate system of justice in sports associations in some matters is crucial and acceptable as long as fundamental values and legal rights are respected. This can be accomplished by converting all sports justice systems to one system, which will ensure an equal case handling for all sorts of athletes as well as leaders, coaches and associations.